PKK violence against civilians: beyond the individual, understanding collective targeting - Masullo, Juan (Terrorism and political violence, 2020)
This article examines the logic of civilian targeting in the Turkish-Kurdish civil war. It analyzes two instances of PKK violence: against pro-state Village Guards’ families in the 1980s and school-teachers in the 1990s. Against original data, we evaluate the extent to which the dominant conceptual tools available in civil war literature help us make sense of these instances and argue that there is a need to go beyond the established selective/indiscriminate distinction if we want to capture the logic of PKK’s targeting. Consequently, we build on and specify further recent conceptual developments in the field and show that both cases are better understood as instances of collective targeting. We further show, however, that the collective nature of each differs in relevant ways: while the killing of the families of Village Guards constitutes an instance of collective targeting in the sense of “extended group association,” in the case of school teachers there are indications of a secondary spatially differentiated selection criteria accompanying the collective logic. Our analysis emphasizes the field’s need for stronger conceptual foundations underpinning our theories of violence against civilians, as well as the limitations of understandings rooted in an “ontological individualism” when applied without careful consideration to non-Western societies.